A Constant Switching Frequency DTC for PMSM Using Low Switching Losses SVM–An Experimental Result - K. Chikh; A. Saad; M. Khafallah; D. Yousfi; F.Z. Tahiri; M. Hasoun (Institute of Advanced Engineering and Science, 2017)
A Constant Switching Frequency Direct Torque Control (CSF-DTC) with low switching losses Space Vector modulation (SVM) for Permanent Magnet Synchronous Motor (PMSM) drive is proposed in this work. The CSF-DTC combines Field Oriented Control (FOC) and basic DTC advantages. Indeed, the proposed control strategy improves the basic DTC performances, which features low flux and torque ripples as well as a fixed switching frequency. The improved DTC ensures also a fast and robust flux and torque responses by using Integral and Proportional (IP) controllers which guaranteed a good disturbance rejection.On the other hand, a symmetrical SVM technique with low switching losses in the PWM inverter is used in order to generate the desired stator voltage vector needed to control the stator flux and the motor torque. Simulation and experimental results are presentedin this paper.These results demonstrate well the performance of the basic and proposed DTC and they show the effectiveness of the constant switching frequency direct torque control.